Management of Systemic Hypersensitivity Reactions to Gonadotropin-Releasing Hormone Analogues during Treatment of Central Precocious Puberty - BEREKET, ABDULLAH; ÖZEN, AHMET OĞUZHAN; BARIŞ, SAFA; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (KARGER, 2020)
Background:Besides local reactions, systemic hypersensitivity reactions such as urticaria, anaphylaxis, serum sickness and Henoch-Schonlein purpura (HSP) have been reported during gonadotropin-releasing hormone (GnRH) analogue treatment.Aim:To present the clinical presentation of 9 cases with systemic hypersensitivity reactions to GnRH analogues and discuss the management of such reactions based on our experience.Patients and Methods:Nine of 232 (3.8%) patients with central precocious puberty receiving GnRH analogue treatment had systemic hypersensitivity reactions in 4 years' period. Six patients had a type 1 hypersensitivity reaction (generalized hives, pruritus, and/or edema) to triptorelin acetate (TA), 2 patients to leuprolide acetate (LA), and 1 patient to both medications who also developed anaphylaxis to LA during intradermal test (IDT). Another patient on TA had skin lesions suggestive of HSP. GnRH analogue treatment was discontinued in 2 patients after discussion with the parents. Treatment was changed to another GnRH analogue preparation in 6 patients and was maintained with the same medication with antihistamines and corticosteroid premedication in 1 patient. None of the patients developed new reactions after these precautions.Conclusion:Systemic hypersensitivity reactions should be carefully evaluated and cross-reaction to the other GnRH analogues should be kept in mind. Discontinuation of GnRH analogue is always an option. However, if continuation of GnRH analogue is elected, we recommend switching to an alternative GnRH analogue, which should be considered only after a skin prick test (SPT) and IDT. In the lack of the possibility to perform SPT and IDT, injections may be administered under strict medical supervision in a well-equipped facility to manage anaphylaxis. We discuss additional options in situations where alternative GnRH analogues are unavailable, which enabled us to continue treatment in most cases without further problems.
Keywords: Adverse reactions; Anaphylaxis; Central precocious puberty; Drug-related side effects; Gonadotropin-releasing hormone analogues; LEUPROLIDE ACETATE; RECURRENT ANAPHYLAXIS; TRIPTORELIN